2015
DOI: 10.1089/zeb.2014.1008
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Oxygen Consumption, and Behavioral Responses of Danio rerio to Variation in Dietary Protein and Lipid Levels

Abstract: In recent years, there has been increasing interest in the welfare of ornamental fish. Diet can significantly impact the welfare of fish, which can manifest as changes in the fish's physical health and behavior. The zebrafish, Danio rerio, is a popular ornamental species; however, little is known about their nutritional requirements with possible implications for their welfare. Here, we investigated the effect of diets with increasing crude protein (iso-caloric diets) and lipid (iso-nitrogenous diets) on the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
(50 reference statements)
1
18
2
Order By: Relevance
“…Similar concerns regarding nutritional requirements and diet standardization were addressed in rodent models several decades ago, leading to the development and adoption of standardized reference and open formulation diets of specific composition. 11 As observed in mammals, specific nutrients and dietary ingredients, or the lack thereof, can potentially alter physiology, behavior, and/or molecular pathways in zebrafish, [12][13][14][15][16][17][18][19][20][21][22][23][24][25] whereas other researches suggested that nutrient content of diets fed to adult zebrafish can even influence the development and health of their offspring. [26][27][28][29][30][31] All these evidences suggest that for zebrafish, diet is an important environmental factor that can potentially compromise and confound outcomes related to the question of study; Therefore, a lack of nutritional control in zebrafish laboratories could affect the interpretation of both past and future research.…”
Section: Introductionmentioning
confidence: 99%
“…Similar concerns regarding nutritional requirements and diet standardization were addressed in rodent models several decades ago, leading to the development and adoption of standardized reference and open formulation diets of specific composition. 11 As observed in mammals, specific nutrients and dietary ingredients, or the lack thereof, can potentially alter physiology, behavior, and/or molecular pathways in zebrafish, [12][13][14][15][16][17][18][19][20][21][22][23][24][25] whereas other researches suggested that nutrient content of diets fed to adult zebrafish can even influence the development and health of their offspring. [26][27][28][29][30][31] All these evidences suggest that for zebrafish, diet is an important environmental factor that can potentially compromise and confound outcomes related to the question of study; Therefore, a lack of nutritional control in zebrafish laboratories could affect the interpretation of both past and future research.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results reported by Akpιnar et al (2012) and Fernandes et al (2016), who observed an inverse relation between feed intake and dietary protein in juvenile shi drum (Umbrina cirrosa) and zebrafish. This phenomenon could be attributed to compensatory response to get more protein in fish fed lower dietary protein levels, as argued by several authors (Akpιnar et al 2012;El-Dakar et al 2011;Fernandes et al 2016;O'Brine et al 2015). Therefore, at restricted feeding regimes at the estimated requirement level in this study fish may not meet their daily protein requirements and significant attention should be paid to feeding levels in zebrafish laboratories.…”
Section: Discussionmentioning
confidence: 91%
“…The natural diet of fishes is incredibly diverse and yet most commercial fish diets were originally formulated for aquaculture and are aimed at carnivorous species of fish with requirements of up to 50% protein and 20% lipid (Halver & Hardy, 2002). While some fish food manufacturers will take into account the different requirements of particular fish species, most commercially available diets are unlikely to be suitable for all fish species (O'Brine et al, 2015). Additionally, in their natural environment fishes can show seasonal changes in food intake which is rarely considered under laboratory conditions.…”
Section: Quality Of Water and Foodmentioning
confidence: 99%